PERANCANGAN SISTEM INFORMASI AKADEMIK PERGURUAN ADVENT CIMINDI BERBASIS WEB DENGAN SMS GATEWAY - Adi Syaputra Simanjuntak (TeIKa, 2021)
Information systems in a school are needed in storing data and sending a report to parents. Cimindi advent college is a school with national standards and also has hundreds of students in it. Academic data collection with such a large amount and the desire of parents to be able to receive information about their children at school may be difficult from the school to carry out their duties. Academic Information System for Advent Cimindi College based on SMS Gateway is an information system that provides academic data processing for Advent Cimindi College students. This research was conducted to create a student data processing system and sending student information to parents via SMS from the system. This information system was created with the Laravel framework. This study produced features that can help in processing student data such as inputting student grades, inputting student absences, inputting tuition payment reports, and sending information to parents. In the future, this feature is expected to be developed in connection with transactions such as student finance.